Supported Single Atom Catalysts for C−H Activation: Selective C−H Oxidations, Dehydrogenations and Oxidative C−H/C−H Couplings - Martín, Nuria; Cirujano, Francisco G. (ChemCatChem, 2021)
The activation of C−H bonds in hydrocarbons (saturated, unsaturated and aromatics) by single atom catalysts immobilized in a solid support is an active research front in catalysis. On the one hand, different examples of transition metal catalysts atomically dispersed on inorganic, organic and hybrid supports are constantly designed, synthesized and characterized using advanced microscopy and spectroscopic techniques. On the other hand, active, selective and stable single metal sites are recently developed as high performant heterogeneous catalysts for the C−H activation of organic molecules. This review covers recent examples of selective alkane and arene C−H oxidations, dehydrogenations of alkanes, as well as C−H/C−H oxidative couplings involving arenes, alkenes and alkynes, based on the use of supported single atom catalysts. Single Atom Catalysis: Single Atom Catalysts immobilized on a support are promising heterogeneous catalysts for the C−H bond activation of hydrocarbons during the synthesis of industrially relevant organic molecules. From alkanes to alkynes and from alkenes to arenes, this review highlights the last advances on the use of atomically dispersed metals on inorganic and organic‐inorganic supports for selective C−H oxidation, dehydrogenation and C−C oxidative coupling steps of basic organic compounds.